1990
DOI: 10.1093/infdis/162.5.1075
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylated Oligosaccharides of Human Milk Protect Suckling Mice from Heat-Stabile Enterotoxin of Escherichia coli

Abstract: Human milk protects suckling mice from the diarrheagenic effects of heat-stabile enterotoxin of Escherichia coli (ST). To identify the human milk fraction responsible for this protection, pooled skimmed, deproteinated milk was passed through charcoal, whereupon lactose was separated from the oligosaccharides. The oligosaccharides contained ST-protective activity; the lactose did not. The neutral, but not the acidic, fraction exhibited protective activity against ST (22% vs. 57% mortality, respectively; P less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(72 citation statements)
references
References 46 publications
1
71
0
Order By: Relevance
“…The metabolic activity of these organisms reduces the colonic pH, which has the effect of inhibiting the proliferation of pathogenic organisms such as Shigella flexneri and Escherichia coli (Gopal and Gill, 2000). In addition, because HMOs are similar in structure to glycoconjugates on the surface of gastrointestinal cells, they are likely to act as soluble receptor analogues; they compete with pathogenic bacteria, bacterial toxins and viruses for attachment to gastrointestinal receptor sites and thus inhibit their actions (Newburg et al, 1990;Cravioto et al, 1991;Cervantes et al, 1995). It seems very likely that the role of anti-infection factors is shared by the milk oligosaccharides of non-human species (Martin et al, 2002).…”
Section: Evolution Of Milk Oligosaccharides and Lactosementioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic activity of these organisms reduces the colonic pH, which has the effect of inhibiting the proliferation of pathogenic organisms such as Shigella flexneri and Escherichia coli (Gopal and Gill, 2000). In addition, because HMOs are similar in structure to glycoconjugates on the surface of gastrointestinal cells, they are likely to act as soluble receptor analogues; they compete with pathogenic bacteria, bacterial toxins and viruses for attachment to gastrointestinal receptor sites and thus inhibit their actions (Newburg et al, 1990;Cravioto et al, 1991;Cervantes et al, 1995). It seems very likely that the role of anti-infection factors is shared by the milk oligosaccharides of non-human species (Martin et al, 2002).…”
Section: Evolution Of Milk Oligosaccharides and Lactosementioning
confidence: 99%
“…Human milk contains approximately 7% of carbohydrate, which is composed of 80% lactose and 20% HMO. The existence of 200 varieties of HMOs has been suggested by mass spectrometry (Ninonuevo et al, 2006), of which 115 structures have been characterized to date; these are classified into 13, depending on their core structures (Kobata, 2010;Urashima et al, 2011). It has been shown that Fuc(a1 -2)Gal(b1 -…”
Section: Evolution Of Milk Oligosaccharides and Lactosementioning
confidence: 99%
“…Although not involved in the binding of SC to IgA (9), the carbohydrate component has other important functions. In vivo studies have demonstrated the protective effects of fucosylated oligosaccharide fractions of human milk against heat stable enterotoxin of Escherichia coli in suckling mice (10). Clostridium difficile binds to glycosylated SC to a much greater extent than to the deglycosylated form (11), and the SC-dependent inhibition of adhesion of enterotoxic forms of E. coli to erythrocytes is apparently reliant on the carbohydrate portion of SC (12).…”
Section: S Ecretory Component (Sc)mentioning
confidence: 99%
“…The neutral oligosaccharides, especially, have been suggested to play an important role in prophylaxis against many pathogens (Newburg, 1997). For example, fucosyloligosaccharides have been shown to inhibit the diarrhea caused by the action of the heat stable toxins of Escherichia coli, Campylobacter jejuni, Calicivirus, Salmonella fyris and Vibrio cholerae (Newburg et al, 1990;Morrow et al, 2004;Coppa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%